When should executives be responsible for corporate acts?: A comment on 'Loeppky et al v Taylor McCaffrey LLP' - MacPherson, Darcy L (Manitoba law journal (1966), 2022)
A recent Manitoba case has forced the Court of Queen's Bench to tackle the thorny issue of director liability for corporate acts. The case of 'Loeppky et al. v Taylor McCaffrey LLP' et al. has already been the subject of a blog, with respect to the some of the main issues in the case. The current contribution, on the other hand, deals with what is one of the subsidiary issues in the case, namely, the bases upon which corporate directors and officers might be held liable for what would otherwise be corporate acts. After all, many corporate executives are legitimately concerned about avoiding personal liability. This case provides further illustration of the fact-dependent nature of finding personal liability of executives for corporate acts.